Sistem Penentuan Bonus Karyawan menggunakan Metode Simple Additive Weighting - Dwi Putri; William Ramdhan; Masitah Handayani (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
The Simple Additive Weighting (SAW) method is one of the methods in determining decisions based on predetermined criteria, such as employee annual bonuses.  However, there are no criteria and systems used to determine who employees are eligible for the yearly bonus based on their purpose The purpose of this study is to create a system of supporting employee annual bonus decisions by applying the SAW method. The waterfall is a model used to build this system through analysis, design, implementation, and testing.  Data collection used observations and interviews, as well as data used by 20 people.  The data analysis technique uses the SAW method by looking at alternatives and rankings of the results obtained.  Testing this system uses a black box by looking at the processes and functions of several components in this system.  These findings result in a system that can provide a decision to determine annual bonuses for employees using the SAW method addition, has been successfully implemented with this method.  In addition, this system also has all its components already functioning, both from the login process to being able to produce feasible decisions and not determining the bonus.